Formation of gadolinium-ferritin from clinical magnetic resonance contrast agents - Neburkova, Jitka; Rulseh, Aaron M; Chang, Shery L Y; Raabova, Helena; Vejpravova, Jana; Dracinsky, Martin; Tarabek, Jan; Kotek, Jan; Pingle, Mohan; Majer, Pavel; Vymazal, Josef; Cigler, Petr (Nanoscale advances, 2020)
Gadolinium deposition in the brain following administration of gadolinium-based contrast agents (GBCAs) has led to health concerns. We show that some clinical GBCAs form Gd3+-ferritin nanoparticles at (sub)nanomolar concentrations of Gd3+ under physiological conditions. We describe their structure at atomic resolution and discuss potential relevance for clinical MRI.